Golden Bakery / Faris Aizuddin Abd Samat ... [et al.] - Abd Samat, Faris Aizuddin; Ahmad Azmi, Ikhmal Aidel; Long Hamdan, Nan Haleeza Izni; Rosram, Nornatrah Hanis; Mohd Yusof, Siti Hajar (2021)
Golden Bakery provides a wide range of cakes, breads, and desserts to customers to ensure their complete satisfaction. Golden Bakery's target customers are all ages, and they include middle-and low-income earners who want to buy products at a reasonable price but with high quality. Aside from that, we target the busiest workers because we also deliver our products to customers' homes. Customers like to visit and buy from our bakery because the service that we provide is quick and friendly. When dealing with customers, we can also give them as an added value. Our company is based in Kuala Lumpur and was. Since its inception in 2020, Golden Bakery has been one of the most popular and preferred desserts. The demand for their desserts and cakes has been increasing because most customers want these desserts and cakes to be served at events or special occasions such as wedding receptions. One of the reasons it is well-known among people, particularly chocolate lovers, is that we introduce premium chocolate, the majority of which is imported from overseas, and we also serve fresh bread from the oven to customers. As a result, customers will be more inclined to purchase our products. Despite the fact that this business has a number of issues, the owners and employees have managed to find a solution. Finally, Golden Bakery will continue to provide the best and highest-quality desserts to all people while providing the best customer service.